El medievalismo fértil de Paloma Díaz-Mas - Rafael M. Mérida Jiménez (Universitat de Barcelona, 2001)
The author of this article is concerned with trying to understand why Paloma Díaz-Mas, the writer of such an excellent novel as La tierra fértil (1999), has not received much critical attention. He underlines three main reasons. First, she does not live in Madrid or Barcelona and so she is far away from the main centres of cultural power. Second, she teaches Spanish literature in the Basque Country, a political and linguistic community which significantly differs from that of many other writers. Third, she writes historical novels, which does not appear to be very fashionable in Spain these days. Moreover, Díaz-Mas is a woman writer who does not make use of the most commonly available feminine patterns, and she does not seem to offer a model easy to include in a given feminist methodology either. However, Mérida-Jiménez argues that Paloma provides an intelligent deconstruction of “male authority” through subtle rhetorical means, as well as a representation of the weakness of his “domination” in very innovative ways, such as those derived from the dialectics between history and fiction, centrality and marginality, heterosexuality and homosexuality, individual and society, dream and reason or tradition and modernity.